LOCAL ISLAMIC RELIGIOUS LEADERS IN ISLAMIZATION IN BANYUMAS (Paramita: Historical Studies Journal, 2019)
In the writing of Islamic-history-themed local history, especially for the Islamic missionary, there is only a small number found, including in Banyumas. Oral tradition and historical sources in the folklore form are found abundantly in the Banyumas Residency in the form of local chronicles. Sheikh Jambu Karang and Prince Mahdum Husen were the oldest Islamic religious leaders who lived in the pre-Demak period or Sundanese kingdom, while PrinceWali Prakosa, Prince Mahdum Cahyana, Prince Mahdum Wali, Prince Senapati Mangkubumi I, and Wirakencana played their roles in Islamizing people in Demak era. Meanwhile, Ki Ageng Gumelem was the Islamic religious leader in the Mataram era. Local legitimacy stated that Sheikh Jambu Karang embraced Islam by a friend of the Prophet Muhammad (peace be upon him), named Prince Attasangin. Prince Wali Prakosa was legitimized as a local Islamic religious leader who participated in building the Great Mosque of Demak, even he was the maker of the Saka tatal. Prince Senapati Mangkubumi, according to the text of Babad Pasir, also helped in building the Great Mosque of Demak and Islamized residents in the inland of East Java and West Java.Keywords: Islamic history, oral tradition, folklore, local Islamic religious leaders, legitimacyÂ Â Dalam penulisan sejarah lokal bertema sejarah Islam, khususnya bagi misionaris Islam, hanya ada sejumlah kecil yang ditemukan, termasuk di Banyumas. Tradisi lisan dan sumber sejarah dalam bentuk cerita rakyat banyak ditemukan di Kediaman Banyumas dalam bentuk kronik lokal. Sheikh Jambu Karang dan Pangeran Mahdum Husen adalah pemimpin agama Islam tertua yang hidup di masa pra-Demak atau kerajaan Sunda, sementara Pangeran Wali Prakosa, Pangeran Mahdum Cahyana, Pangeran Mahdum Wali, Pangeran Senapati Mangkubumi I, dan Wirakencana memainkan peran mereka dalam mengislamkan orang-orang di era Demak. Sementara itu, Ki Ageng Gumelem adalah pemimpin agama Islam di era Mataram. Legitimasi lokal menyatakan bahwa Syekh Jambu Karang memeluk Islam oleh seorang teman Nabi Muhammad SAW, bernama Pangeran Attasangin. Pangeran Wali Prakosa dilegitimasi sebagai pemimpin agama Islam setempat yang berpartisipasi dalam membangun Masjid Agung Demak, bahkan ia adalah pembuat Saka tatal. Pangeran Senapati Mangkubumi, menurut teks Babad Pasir, juga membantu membangun Masjid Agung Demak dan penduduk yang terislamisasi di pedalaman Jawa Timur dan Jawa Barat.Kata kunci: Sejarah Islam, tradisi lisan, cerita rakyat, tokoh agama Islam setempat, legitimasiÂ